Detection of endometrial and subendometrial vasculature on the day of embryo transfer and prediction of pregnancy during fresh in vitro fertilization cycles - Ari Kim; Hyuk Jung; Won June Choi; Sung Nam Hong; Heung Yeol Kim (Taiwanese Journal of Obstetrics & Gynecology, 2014)
Objectives: Successful implantation depends on interaction between a blastocyst and a receptive endometrium. Endometrial vasculature is important in the early endometrial response to blastocyst implantation, and vascular changes can affect uterine receptivity. This study aims to investigate whether vascular parameters measured using three-dimensional power Doppler ultrasound (3D PD-US) could predict pregnancy following fresh in vitro fertilization and embryo transfer (IVF–ET) using a gonadotropin releasing hormone (GnRH) agonist long protocol. Materials and methods: This prospective observational study enrolled 236 nulliparous women who underwent a first IVF–ET using a GnRH long protocol with stimulation by recombinant FSH (rFSH) from May 2009 to April 2012. After excluding two cases of tubal pregnancy, 234 women were in either a pregnant group (n = 113) or a nonpregnant group (n = 121). Color Doppler ultrasound and 3D PD-US examinations were performed on the day of embryo transfer. Main outcomes were pulsatility index (PI), resistance index (RI), systolic/diastolic ratio (S/D) of the uterine artery, vascularization index (VI), flow index (FI), and vascularization flow index (VFI) of the endometrium and subendometrial region. Measurements were analyzed relative to IVF–ET outcome (pregnant vs. nonpregnant). Results: No significant differences were observed in patient age, infertility duration, body mass index (BMI), basal FSH levels, number of retrieved oocytes or good quality embryos, or endometrial thickness or volume between the two groups. The pregnant group had higher endometrial VI, FI, and VFI scores than the nonpregnant group (p = 0.001, p = 0.000, p = 0.021, respectively). By contrast, neither subendometrial region VI, FI, and VFI scores (p = 0.770, p = 0.252, p = 0.451), nor uterine artery PI, RI, or S/D scores (p = 0.256, p = 0.527, p = 0.365) differed between groups. Cut-off values of endometrial VI, FI, and VFI scores were 0.95, 12.94, and 0.15 for pregnancy achievement. Conclusion: Three dimensional PD-US was a useful and effective method for assessing endometrial blood flow in IVF cycles. Good endometrial blood flow on the day of embryo transfer might be associated with high pregnancy success with a GnRH long protocol, because this is indicative of endometrial receptivity in fresh IVF cycles.